Malaysian studies pocket read / Ani Juaini Bahrin ... [et al.] - Bahrin, Ani Juaini; Yaakub, Farhana; Sufian, Firdausi; Abbdullah, Nurfaizah; Jalil, Saiful Zizi (2021)
People say attending university is a great learning opportunity due to the fact that the students are given the chance to explore and gain new enriching experience. Sometimes it could be an adventurous journey for the new students where it offers a hectic experience that is more than what they had in mind. The university is where the students try to make new friends and fit in and at times, some need to learn how to manage their money especially for their food and public transportation. Some students might even struggle to cook their own proper meals while undergoing meaningful university’s events and programs in one semester. With all that in hands, they must not forget their main agenda in university; exploring and digesting new topics, making sense of the unfamiliar terms in their chosen fields, and trying to excel. In a study conducted by Alfan and Othman (2005), it was found that knowledge prior to entering the university is crucial in assisting the student to undertake the chosen courses. In addition, based on the study conducted by Perander et al (2021) the main findings confirmed that starting studies in higher education is challenging for many students. Therefore in order to address negative emotional learning experience among students especially those taking public administration related subjects, Malaysian Studies Pocket Read was created with high anticipation that it can ease the students understanding and unfamiliarity upon terms, related policies, government structure and issues related with national concern. The pocket read came in a petite size, handy and to make it different with other books in public administration, it will be using infographics to explain various terms and policies. The recent study conducted by Becerra-Rodríguez et al (2021) shows that there is a significant improvement in learning scientific topics by using infographics construction. The findings also has been supported by Ozdamli et al.(2016), saying that students think that using infographics are more understandable and more satisfactory. Moreover, since infographics are easier to remain in minds, it was hope that this kind of teaching method can be more effective and gratifying.